An in vivo analysis of the effect and duration of treatment with botulinum toxin type A using digital image speckle correlation. Issue 3 (8th April 2013) - Bhatnagar, Divya; Conkling, Nicole; Rafailovich, Miriam; Phillips, Brett T.; Bui, Duc T.; Khan, Sami U.; Dagum, Alexander B.
<x xml:space="preserve">Abstract</x> Background Use of Botulinum toxin type A (BTX‐A) for facial wrinkles is well‐documented, but current methods of subjective evaluation by clinicians and patients fail to objectively quantify the magnitude and duration of facial muscle paralysis. Objective (a) Determine the locus of facial muscular tension; (b) Quantify and monitor muscular paralysis and subsequent return; (c) Continuously correlate the appearance of wrinkles and muscular tension using non‐invasive digital image speckle correlation (DISC) to measure treatment efficacy; (d) Corroborate objective data with existing rating scales (subject global assessment and facial lines outcome‐11). Methods Two sequential images of slight facial motion (frowning, raising eyebrows) are taken with a camera for n = 6 patients pre‐ and post‐treatment at different time points up to 24 weeks. DISC processes the images to produce a vector map of muscular displacement to obtain spatially resolved information regarding facial tension. Results We observed maximum paralysis (≥70%) at 2 weeks, and the rate of recovery varied widely ranging from 2 to 5 months, with two patients continuing to exhibit reduced contraction at 24 weeks. Vector analysis of pre‐treatment contraction correctly predicted injection site and illustrated lines of maximum tension. Conclusions Digital image speckle correlation can precisely track the degree of contraction of different muscle groups following BTX‐A injection. It can help predict injection site, quantify muscle paralysis, and monitor the recovery following BTX‐A injection. Results were found to be reproducible across six patients.